Physical activity and subjective well-being of older adults during COVID-19 prevention and control normalization: Mediating role of outdoor exercise environment and regulating role of exercise form - Yang, Qingqing; Tang, Yue; Jennings, George; Zhao, Bin; Zhu, Fusheng; Ma, Xiujie (Frontiers in Psychology, 2022)
Since the outbreak of the COVID-19 epidemic, the physical and mental health of the elderly has been threatened. Promoting physical and mental health through physical activity has therefore become a strategy for healthy ageing. In order to better understand the impact of the participation of the elderly in physical activity, this paper selects different types of physical activity, and examines the relationship between different physical activities and subjective well-being through the analysis of mediation effect of outdoor exercise environment and regulation effect of exercise form. 903 elderly people were surveyed using the Physical Activity Scale, Memorial University of Newfoundland Scale of Happiness (MUNSH), the Exercise Environment Scale, and the Exercise Form Scale. SPSS was used for statistical analysis, while linear regression analysis was adopted for processing data, and AMOS used to establish a moderation model. The results showed that: (1) Different physical activities showed significant positive correlations with all dimensions of subjective well-being, while Tai Chi had the strongest significance for subjective well-being in the elderly; (2) The level of subjective well-being of the elderly engaging in moderate and intense exercises is higher than that of those in mild exercises; (3) The outdoor exercise environment plays a mediation role between different physical activities and subjective well-being; (4) Exercise forms have a regulation effect on the subjective well-being of the elderly in different physical activities, and walking & jogging produces the strongest regulation effect. The study results reveal the working mechanisms of different physical activities on the subjective well-being of the elderly during the normalization of the epidemic, expands the research scope of outdoor exercise environment, and provides practical implications for the intervention of subjective well-being.